1997
DOI: 10.1016/s0360-3016(97)00333-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between thermal dose and outcome in thermoradiotherapy treatments for superficial recurrences of breast cancer: Data from a phase III trial

Abstract: Relationship between thermal dose and outcome in thermoradiotherapy treatments for superficial recurrences of breast cancer: data from a phase III trial Sherar, M.; Liu, F.F.; Pintilie, M.; Levin, W.; Hunt, J.; Hill, R.; Hand, J.; Vernon, C.; van Rhoon, G.; van der Zee, J.; González González, D.; van Dijk, J.D.P.; Whaley, J.; Machin, D. Published in:International Journal of Radiation Oncology Biology Physics DOI:10.1016/S0360-3016(97)00333-7 Link to publicationCitation for published version (APA): Sherar, M., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
133
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 164 publications
(137 citation statements)
references
References 25 publications
(5 reference statements)
3
133
1
Order By: Relevance
“…29 Hyperthermia has been demonstrated in Phase III randomized trials to benefit patients with both improved local control 1,4,5 and survival. 2 However, attainment of uniform temperature within the target tumor tissues is difficult to achieve, 30 hence any additional therapeutic manoeuvre that could enhance heat-induced cytotoxicity would be desirable. We have previously demonstrated that PKB can modulate heat sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…29 Hyperthermia has been demonstrated in Phase III randomized trials to benefit patients with both improved local control 1,4,5 and survival. 2 However, attainment of uniform temperature within the target tumor tissues is difficult to achieve, 30 hence any additional therapeutic manoeuvre that could enhance heat-induced cytotoxicity would be desirable. We have previously demonstrated that PKB can modulate heat sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…(104) This parameter, cumulative equivalent minutes at 43°C achieved by 90% of the measured temperate points in the targeted area or CEM43T90, has been shown in multiple studies to correlate with clinical outcome. (83)(84)(105)(106)(107)(108)(109)(110)(111)(112) The field of thermal dosimetry continues to evolve given that most treatment thermal profiles are based on modest samples of temperature points in the heated region. Non-invasive approaches to temperature measurement capable of monitoring hundreds or thousands of points in real time is now possible albeit not widely available.…”
Section: Challenges To Clinical Implementationmentioning
confidence: 99%
“…Temperature inhomogeneity has been shown to impact on outcome and this is due to technical challenges as well as the heat -sink effects caused by the tumor vasculature. 11,12 The temperatures reached in hyperthermia treatment activate the heat shock response in cells. Certain members of the heat shock gene family are quiescent in resting cells but strongly induced following heat damage.…”
mentioning
confidence: 99%